2015
DOI: 10.1038/ncomms8544
|View full text |Cite
|
Sign up to set email alerts
|

Causative role of left aIPS in coding shared goals during human–avatar complementary joint actions

Abstract: Successful motor interactions require agents to anticipate what a partner is doing in order to predictively adjust their own movements. Although the neural underpinnings of the ability to predict others' action goals have been well explored during passive action observation, no study has yet clarified any critical neural substrate supporting interpersonal coordination during active, non-imitative (complementary) interactions. Here, we combine non-invasive inhibitory brain stimulation (continuous Theta Burst St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
52
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(64 citation statements)
references
References 71 publications
12
52
0
Order By: Relevance
“…Specifically, some have suggested that, during imitation, the left POp is involved in comparing information about the imitator's body with the observed actor's body (Mengotti et al ., ; Krüger et al ., ) and that activity in this area is correlated with the subsequent accuracy of the imitative action (Krüger et al ., ). The left aIPS, however, has been suggested to guide object‐directed hand movements (Tunik et al ., ) and, importantly, also appears to represent the goals of observed object‐directed actions (Hamilton & Grafton, , ; Hamilton, , ; Sacheli et al ., ). As such, the aIPS could support the imitation of object‐directed actions because it ostensibly provides a ‘common representational system for the actions of self and other’ (p. T84, Tunik et al ., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, some have suggested that, during imitation, the left POp is involved in comparing information about the imitator's body with the observed actor's body (Mengotti et al ., ; Krüger et al ., ) and that activity in this area is correlated with the subsequent accuracy of the imitative action (Krüger et al ., ). The left aIPS, however, has been suggested to guide object‐directed hand movements (Tunik et al ., ) and, importantly, also appears to represent the goals of observed object‐directed actions (Hamilton & Grafton, , ; Hamilton, , ; Sacheli et al ., ). As such, the aIPS could support the imitation of object‐directed actions because it ostensibly provides a ‘common representational system for the actions of self and other’ (p. T84, Tunik et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in research with both healthy individuals and apraxia patients, there is little use of motion-tracking for characterising imitation in an objective fashion (with some exceptions, e.g. Braadbaart et al, 2012;Campione & Gentilucci, 2011;Gold et al, 2008;Hayes et al, 2016;Hermsd€ orfer et al, 1996;Kr€ uger et al, 2014;Pan & Hamilton, 2015;Reader & Holmes, 2015;Sacheli et al, 2012Sacheli et al, , 2013Sacheli et al, , 2015aWild et al, 2010;Williams et al, 2013), despite the fact that kinematics are an important element of social interactions (Krishnan-Barman et al, 2017). With this in mind, we used a two-person motion-tracking approach in this experiment to better understand the links between actor and imitator behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…In one example TMS was used to great effect with a virtual character (Sacheli et al 2015a). Further development of neurostimulation methods alongside two-person or virtual character experimental designs would add greater depth to the growing research on neural aspects of social interaction by allowing us to examine cause-and-effect detail regarding certain brain areas and their role in realistic social interaction.…”
Section: Improving Methodologymentioning
confidence: 99%
“…Such paradigms have shown that corticospinal facilitation during action observation is effector‐specific (Strafella & Paus, ; Romani et al ., ; Urgesi et al ., ,b; Alaerts et al ., ), anticipates the time‐course of action kinematics (Urgesi et al ., ) and is influenced by whether the observed action is successful (Aglioti et al ., ; Candidi et al ., ). Importantly, these findings highlight characteristics of sensorimotor simulation that can be crucial in other social contexts, such as when coordinating with a partner during joint action (Knoblich & Jordan, ; Bekkering et al ., ; Vesper et al ., , ; Sacheli et al ., ). On the contrary, in our ‘social’ context we find evidence in favour of an unspecific, general facilitation that is independent from the specific motor behaviour observed by the participant.…”
Section: Discussionmentioning
confidence: 97%